2014
DOI: 10.1002/stem.1707
|View full text |Cite
|
Sign up to set email alerts
|

YB-1 Transforms Human Mammary Epithelial Cells Through Chromatin Remodeling Leading to the Development of Basal-Like Breast Cancer

Abstract: There is growing evidence that cancer-initiation could result from epigenetic changes. Y-box binding protein-1 (YB-1) is a transcription/translation factor that promotes the formation of tumors in transgenic mice; however, the underlying molecular events are not understood. To explore this in a human model system, YB-1 was expressed in mammary epithelial cells under the control of a tetracycline-inducible promoter. The induction of YB-1 promoted phenotypes associated with malignancy in three-dimensional breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 55 publications
1
45
1
Order By: Relevance
“…It was later discovered that YB-1 induces cytokinesis failure in human mammary epithelial cells, thereby promoting numerical CA, but also limits centrosome size, thereby restraining abnormal amplification of centrosome volume. It additionally induces aneuploidy, dicentric chromosomes and double minutes, extensive chromosome breakage, defective sister chromatid cohesion, and HER amplification (Davies, et al 2011), although a subsequent study found that YB-1 induces triple-negative mammary tumor formation (Davies, et al 2014). Although YB-1 induces numerical CA, it also promotes extensive chromatin remodeling and the development of stem-like properties (Davies et al 2014), and it binds to the promoter of various genes that drive proliferation (e.g., the genes encoding EGFR, HER2, cyclin A, and cyclin B1) (Davies et al 2011), so the relative contribution of CA to YB-1-induced breast tumorigenesis is hard to decipher from this study alone.…”
Section: Centrosome Amplification and Breast Tumorigenesismentioning
confidence: 99%
“…It was later discovered that YB-1 induces cytokinesis failure in human mammary epithelial cells, thereby promoting numerical CA, but also limits centrosome size, thereby restraining abnormal amplification of centrosome volume. It additionally induces aneuploidy, dicentric chromosomes and double minutes, extensive chromosome breakage, defective sister chromatid cohesion, and HER amplification (Davies, et al 2011), although a subsequent study found that YB-1 induces triple-negative mammary tumor formation (Davies, et al 2014). Although YB-1 induces numerical CA, it also promotes extensive chromatin remodeling and the development of stem-like properties (Davies et al 2014), and it binds to the promoter of various genes that drive proliferation (e.g., the genes encoding EGFR, HER2, cyclin A, and cyclin B1) (Davies et al 2011), so the relative contribution of CA to YB-1-induced breast tumorigenesis is hard to decipher from this study alone.…”
Section: Centrosome Amplification and Breast Tumorigenesismentioning
confidence: 99%
“…YB-1 overexpressed cells were seen to have phenotypic changes such as formation of acini with lumen along with the expression of tumor initiation cell markers i.e. CD44, CD49f and BMI1 were expressed in earlier YB-1 overexpressed luminal cells (Davies et al, 2014).…”
Section: Yb-1 and Breast Cancermentioning
confidence: 99%
“…A comparative in vitro study on Tet-repressed YB-1 (HTRY) human mammary epithelial cells (HMECs) expressing YB-1 and Tet-repressed Lac-Z (HTRZ) LacZexpressing control cell line showed an up-regulated YB-1 in HTRY cell lines as compared to HTRZ cell lines (Davies et al 2014). The study was conducted to study the transformation of human mammary epithelial cells into BLBC.…”
Section: Yb-1 and Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations